2020
DOI: 10.1515/jpem-2020-0174
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E and TERT promoter mutations in paediatric and young adult papillary thyroid cancer and clinicopathological correlation

Abstract: ObjectivesThe primary objective of this study was to determine the prevalence of BRAFV600E and TERTpromoter mutations in paediatric and young adult patients with papillary thyroid carcinoma (PTC) and the secondary objective, to assess their association with clinicopathological features.MethodsPatients ≤20 years who underwent surgery for differentiated thyroid cancer (DTC) from 2005 to 2018 were consecutively enrolled for BRAFV600E and TERTpromoter mutations analysis and records analysed for the association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
12
0
2
Order By: Relevance
“…Our results suggested 30 years might be a more appropriate cutoff age for predicting the risk for CLNM among Chinese patients. The results of a previous study indicated that the frequency of lymph node metastasis was 67% (64/95) in pediatric and young adult PTC patients (age ≤ 20 years) [ 17 ]. The correlation between age and CLNM needs to be further studied in a larger population.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested 30 years might be a more appropriate cutoff age for predicting the risk for CLNM among Chinese patients. The results of a previous study indicated that the frequency of lymph node metastasis was 67% (64/95) in pediatric and young adult PTC patients (age ≤ 20 years) [ 17 ]. The correlation between age and CLNM needs to be further studied in a larger population.…”
Section: Discussionmentioning
confidence: 99%
“…This multivariate analysis revealed RAI refractoriness to be significantly associated with BRAF V600E mutation. However, none of the 17 patients with distant metastases had BRAF V600E mutation, and there was a lack of any significant association of BRAF V600E mutation with the status of disease recurrence or progression [ 71 ]. Contrasting results were reported by Alzahrani, who found persistent/recurrent disease to be significantly more common in patients with BRAF V600E mutation than in those without [ 7 ].…”
Section: Molecular Profile Of Differentiated Thyroid Carcinomasmentioning
confidence: 99%
“…None of their pediatric patients had this alteration [ 63 ]. In a recent study from India, none of the 98 patients harbored TERT promoter mutations [ 71 ]. In another study based on 81 sporadic pediatric PTC patients from Japan, TERT promoter mutations were absent in all [ 65 ].…”
Section: Molecular Profile Of Differentiated Thyroid Carcinomasmentioning
confidence: 99%
“…The only test that can detect increased risk of malignancy is molecular testing (BRAF V600E , RET/PTC gene and NTRK–fusion) [ 7 ]. In the case of inconclusive molecular testing or if those tests are unavailable, diagnostic lobectomy is an appropriate surgical option.…”
Section: Introductionmentioning
confidence: 99%